ERROR ON THE USE OF NOUN PHRASE MADE BY THE ELEVENTH GRADE OF MADRASAH ALIYAH BONTOMARANNU - Resky Amaliah; Bahrun Amin; Ratu Yulianti Natsir (Journal of Language Testing and Assessment, 2021)
This thesis study aimed at (1) To find out the students' mistakes from English noun phrases using pre modifiers in writing English texts made by eleventh grade students? (2) To find out students' mistakes from English noun phrases using the post modifier in writing English texts made by eleventh grade students? The research design a descriptive quantitative method, in which it used writing test. The result of the data that the researcher got the most types of error in noun phrase using pre-modifier and post-modifier in disordering made by the students in using noun phrase. The result of the analysis indicated that there are two part the student made error for the first is using pre-modifier in determiner is 66 errors or 66%, in adjective 9 errors or 9%, in Quantifier 1 error or 1%. The second is using post-modifier in adjective, 14 errors or 14%, in To-Infinitive 1 error or 1% and the last is prepositional phrase with 10 errors or 10%. This mean that there was high level error in noun phrase using pre-modifier and post-modifier at Madrasah Aliyah Bontomarannu. Keywords: Error analysis, Noun Phrase, Writing skills.